Role of mitochondria transmembrane potential in lymphocyte apoptosis - Jaffar, Israa F. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Mitochondria play an important role in the regulation of physiological type of cell death (Apoptosis) this type of cell death can be stimulated by two major pathways: external (Fas-Fas ligand interaction) and internal mitochondrial pathway which require disruption of mitochondrial transmembrane potential (ΔΨm ) which leads to opening of mitochondrial channels that lead to release of cytochrome –C which would execute apoptotic process. Patients and Methods:The study included 32 normal subjects; 2 ml of venous blood were aspirated from each of them and processed for peripheral blood lymphocytes separation (PBL) Then lymphocyte apoptosis was studied before and after exposing (PBL) to hyperthermia by these three methods to compare which of them can detect earliest apoptotic changes: Cell count and viability, morphological changes (by acredine orange stain) and the changes in mitochondrial membrane potential by Mitolight Apoptosis Detection Kit. Results: Our results showed that the percentage of lymphocyte apoptosis detected by mitolight was significantly higher than those detected by other two methods. Conclusion: This study shows that mitochondrial changes can detect earlier apoptotic process than morphological features detected by DNA stains.